Correlation between a 10‐color flow cytometric measurable residual disease (MRD) analysis and molecular MRD in adult B‐acute lymphoblastic leukemia. Issue 2 (21st November 2021) - Singh, Jasmine; Gorniak, Malgorzata; Grigoriadis, George; Westerman, David; McBean, Michelle; Venn, Nicola; Law, Tamara; Sutton, Rosemary; Morgan, Sue; Fleming, Shaun
Abstract: Background: Measurable residual disease (MRD) monitoring in acute lymphoblastic leukemia (ALL) is an important predictive factor for patient outcome and treatment intensification. Molecular monitoring, particularly with quantitative polymerase chain reaction (qPCR) to measure immunoglobin heavy or kappa chain (Ig) or T‐cell receptor (TCR) gene rearrangements, offers high sensitivity but accessibility is limited by expertise, cost, and turnaround time. Flow cytometric assays are cheaper and more widely available, and sensitivity is improved with multi‐parameter flow cytometry at eight or more colors. Methods: We developed a 10‐color single tube flow cytometry assay. Samples were subject to bulk ammonium chloride lysis to maximize cell yields with a target of 1 × 10 6 events. Once normal maturation patterns were established, patient samples were analyzed in parallel to standard molecular monitoring. Results: Flow cytometry was performed on 114 samples. An informative immunophenotype was identifiable in all 22 patients who had a diagnostic sample. MRD analysis was performed on 87 samples. The median lower limits of detection and quantification were 0.004% (range 0.0005%–0.028%) and 0.01% (range 0.001%–0.07%) respectively. Sixty‐five samples had concurrent molecular MRD testing, with good correlation ( r = 0.83, p < 0.001). Results were concordant in 52 samples, and discordant in 13 samples, including one case where impending relapse was detected by flow cytometry but not Ig/TCR qPCR. Conclusions: Our 10‐color flow cytometric MRD assay provided adequate sensitivity and good correlation with molecular assays. This technique offers rapid and affordable testing in B‐ALL patients, including cases where a suitable molecular assay cannot be developed or has reduced sensitivity.